Five year review of intrauterine contraceptive device use in Federal Medical Centre Owerri, Nigeria - Onyegbule OA; Idih EE; Ododo NA; Nzeribe AE (Ibom Medical Journal, 2017)
Background: Unplanned pregnancy poses a major public health challenge in women of reproductive age, especially in developing countries. The intrauterine device contraceptive (IUCD) is a widely used method of contraception.